Pelaksanaan Manajemen Kurikulum dalam Meningkatkan Mutu Pendidikan di MIS Al-Hikmah Namorambe - Neliwati; Mhd. Alfi Syahrin; Hirwansyah; Indra Sakti Siagian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to evaluate the implementation of curriculum management in improving the quality of education at MIS Al-Hikmah Namorambe. This study uses a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. The results show that well-planned curriculum planning, regular teacher training, and effective supervision significantly contribute to improving the quality of education. Supporting factors such as students, social, political, economic, and technological aspects as well as challenges such as limited facilities and lack of teacher supervision were also identified. In conclusion, good curriculum management implementation, supported by internal and external meetings as well as continuous training and supervision, is effective in improving the quality of education at MIS Al-Hikmah Namorambe.